Motivation, Critical Thinking and Academic Verification of High School Students Information-seeking Behavior - Hidayat, Z; Saefudin, Asep; Sumartono, Sumartono (Record and Library Journal, 2017)
High school students have known as Gen Y or Z and their media using can be understand on their information-seeking behavior. This researchâs purposes were: 1) to analyze the studentsâ motivation; 2) to analyze the critical thinking and academic verification; 3) to analyze the information-seeking behavior. This study used quantitative approach through survey among 1125 respondents in nine clusters, i.e. Central, East, North, West, and South of Jakarta, Tangerang, Bekasi, Depok, and Bogor. Schools sampling based on "the best schools rank" by the government, while respondents have taken by accidental in each school. Construct of questionnaire included measurement of motivation, critical thinking and academic verification, and the information-seeking behavior at all. The results showed that the motivations of the use of Internet were dominated by habit to interact and be entertained while on the academic needs are still relatively small but increasing significantly. Studentsâ self-efficacy, performance and achievement goals tend to be high motives, however the science learning value, and learning environment stimulation were average low motives. High school students indicated that they think critically about the various things that become content primarily in social media but less critical of the academic information subjects. Unfortunately, high school students did not conducted academic verification on the data and information but students tend to do plagiarism.